1995
DOI: 10.1111/j.1749-6632.1995.tb44699.x
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of the Hypothalamic‐Pituitary‐Adrenal Axis against Lethality Produced by Immune, Infectious, and Inflammatory Stress

Abstract: We have shown that ADX and HYPOX rats exhibit a markedly increased sensitivity to the lethal effects of IL-1-beta and LPS compared to sham controls with an intact HPAA. These results indicated that the reports of lethal effects of cytokines and LPS which generates cytokines in mice with a compromised HPAA were not idiosyncratic or specific to mice but represented a general response that would have been expected in any organism with a compromised HPAA. We further demonstrated that protection against lethal effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 75 publications
2
60
0
2
Order By: Relevance
“…12,15 Of note, although not examined in this study, replacement of glucocorticoids in glucocorticoid-deficient animals has been shown to reverse the detrimental consequences of these effects. 13,15 Consistent with the observed changes in the behavior of MCMV-infected mice, a number of studies have found alterations in locomotor and exploratory activity in immune-challenged animals. For example, rats or mice peripherally injected with LPS (i.p.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…12,15 Of note, although not examined in this study, replacement of glucocorticoids in glucocorticoid-deficient animals has been shown to reverse the detrimental consequences of these effects. 13,15 Consistent with the observed changes in the behavior of MCMV-infected mice, a number of studies have found alterations in locomotor and exploratory activity in immune-challenged animals. For example, rats or mice peripherally injected with LPS (i.p.…”
Section: Discussionmentioning
confidence: 71%
“…[4][5][6][7][8][9][10][11][12] Previous work by our group and others has demonstrated that removal of glucocorticoids (via adrenalectomy (ADX)) during viral infection is associated with elevations in plasma and tissue concentrations of proinflammatory cytokines and renders animals more susceptible to septic shock and death. [13][14][15] In addition, in the case of infection with murine cytomegalovirus (MCMV), a cytopathic virus that induces an early natural killer cell-mediated, anti-viral defense accompanied by elevations in plasma TNF-alpha, IL-1 and IL-6, 15 the increased death rate in adrenalectomized, MCMV-infected, animals can be reversed by glucocorticoid replacement. 15 Previous studies also have shown that the MCMV-induced corticosterone response, which parallels peak plasma cytokine concentrations and occurs around 36 h after infection, is dependent on IL-6.…”
Section: Introductionmentioning
confidence: 99%
“…It was beyond the scope of the present study to determine whether short-day increases in corticosterone are maintained throughout the circadian cycle; however, in hamsters short-day increases in cortisol are evident at several phases of the circadian cycle (including shortly before lights-off, as described here) and amplified (SD≫LD) following LPS treatments (Bilbo et al, 2003). Endogenous glucocorticoids have potent inhibitory effects on sickness behaviors (Goujon, et al, 1997), attenuating proinflammatory cytokine production in the periphery (Kapcala et al, 1995;Pezeshki et al, 1996;Goujon et al, 1996), and suppressing expression of proinflammatory cytokines in the CNS (Wisse et al, 2004). In rats, exogenous glucocorticoids also inhibit behavioral and thermoregulatory responses to LPS and IL-1β (McClellan et al, 1994;Morrow et al, 1996;Propes & Johnson, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids exert a negative feedback effect on the inflammatory response by reducing the production, secretion and actions of the principal inflammatory mediators, such as IL-1 , and are widely used clinically as anti-inflammatory agents (Kapcala et al 1995). However, glucocorticoids also inhibit testicular steroidogenesis by actions at the hypothalamus and pituitary (Bambino & Hsueh 1981), and by direct inhibition of P450scc, 3 -hydroxysteroid dehydrogenase and P450c17 levels (Sapolsky 1985, Hales & Payne 1989, Monder et al 1994, Gao et al 1996, acting through specific receptors on the Leydig cells (Stalker et al 1989).…”
Section: Introductionmentioning
confidence: 99%